ANALISIS CASH WAQF LINKED SUKUK (CWLS) DI BADAN WAKAF INDONESIA (BWI): PENDEKATAN MAQASHID SYARIAH IMAM ASY-SYATIBI - Achmad Fachmi; Adi Mansah (Taksasila Edukasi Insani, 2025)
Indonesia holds vast potential in cash waqf development; however, most waqf assets remain underutilized and unproductive. To address this issue, the government—through the Indonesian Waqf Board (BWI)—introduced an innovative instrument known as the Cash Waqf Linked Sukuk (CWLS), which integrates cash waqf with sovereign sukuk to support the financing of social sectors. This study aims to analyze the implementation of CWLS by BWI and assess its alignment with the Maqashid Sharia framework as formulated by Imam Asy-Syatibi. This research employs a qualitative descriptive approach using a case study method. Data were collected through in-depth interviews, observation, and documentation, and analyzed using Miles and Huberman's thematic reduction technique based on the five dimensions of maqashid. The findings reveal that the implementation of CWLS reflects the core principles of maqashid: hifz al-din (protection of religion), hifz al-nafs (protection of life), hifz al-aql (protection of intellect), hifz al-mal (protection of wealth), and hifz al-nasl (protection of lineage). CWLS has made a tangible contribution to the establishment of waqf-based hospitals, provision of scholarships, and community economic empowerment through vocational training and micro-enterprise support. The study concludes that CWLS is a sharia-compliant social finance innovation that holistically embodies maqashid values and offers a strategic solution for advancing productive waqf in Indonesia. The study also recommends enhancing public awareness, transparency, and cross-sector collaboration in future CWLS initiatives.Keywords : Cash Waqf Linked Sukuk, Cash Waqf, Maqashid Sharia, Indonesian Waqf Board, Sovereign Sukuk